2014
DOI: 10.1128/aem.01219-14
|View full text |Cite
|
Sign up to set email alerts
|

Wipes Coated with a Singlet-Oxygen-Producing Photosensitizer Are Effective against Human Influenza Virus but Not against Norovirus

Abstract: bTransmission of enteric and respiratory viruses, including human norovirus (hNoV) and human influenza virus, may involve surfaces. In food preparation and health care settings, surfaces are cleaned with wipes; however, wiping may not efficiently reduce contamination or may even spread viruses, increasing a potential public health risk. The virucidal properties of wipes with a singlet-oxygen-generating immobilized photosensitizer (IPS) coating were compared to those of similar but uncoated wipes (non-IPS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Hygienic wipes containing 16.5% ethanol (Table 1 ) gave the same results as wet wipes. Wiping is a short duration activity and the virucidal effect of disinfectant is required within seconds (Verhaelen et al 2014 ). Ethanol is widely assumed to be very effective against coronaviruses, especially at concentrations of around 70% with a contact time of 30 s or longer (Geller et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hygienic wipes containing 16.5% ethanol (Table 1 ) gave the same results as wet wipes. Wiping is a short duration activity and the virucidal effect of disinfectant is required within seconds (Verhaelen et al 2014 ). Ethanol is widely assumed to be very effective against coronaviruses, especially at concentrations of around 70% with a contact time of 30 s or longer (Geller et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, residual amounts (0.2–0.6% residual virus proportions) of norovirus were found on the steel surfaces. 97 Notably, in this case, no difference was found between the treated and untreated wipes. They further tested the already used wipes (used on steel surfaces) on a secondary steel surface to investigate cross-contamination and revealed that non-enveloped viruses demonstrated cross-contamination.…”
Section: Polymeric and Organic Antiviral Coatingsmentioning
confidence: 65%
“… 96 In another study, wipes with polypropylene fibers were coated with the photosensitizer rose bengal, which is immobilized on the fibers through multiple amide bonds and produces singlet oxygen during exposure to visible light. 97 Wipes were spiked with various viruses including the human norovirus GI.4 and GII.4, murine norovirus 1 (MNV-1), human adenovirus type 5 (hAdV-5), and influenza virus H1N1. The non-enveloped viruses did not exhibit prompt inactivation, with the time needed for the first 1-log reduction being more than 7 h, whereas enveloped viruses showed immediate and complete inactivation (more than 4-log).…”
Section: Polymeric and Organic Antiviral Coatingsmentioning
confidence: 99%
See 2 more Smart Citations